A Reformulation of the Dual Career Conceptual Model for Analysis in an Organizational Scope: Revealing new Aspects - Heliani Berlato; Karen Florencio Corrêa (BBR: Brazilian Business Review)
Couples who live a dual career, in general, are characterized by their continuing professional engagement and their desire for personal growth together. It is a synergy between career aspirations and family sphere, so that they co-exist; reflecting nowadays, a challenge for people who seek to live this duality. Not exempt from it, it is possible to understand the need for management models of people who are in harmony with the desires of dual career couples who are part of organizations. If in the 1980s the existence of dual career couples was not so common in Brazil, nowadays organizations increasingly receive these couples, which impacts the need for people management models to keep up with these social changes. Therefore, the model recognizes that the personal dimension (impacts) on the organizational context cannot be avoided, and also that other factors affect both spheres (personal and organizational) when referring to the normative roles that permeate these areas. The main intention of this essay is to construct a theoretical model of dual career to consider the factor - organization, as vital to understand (and accept) the need to consider other dimensions on the dual career analytical perspective. The first evidences of dual career studies in Brazil revealed that the look at this movement only from the individual's margin is limited. This way, to consider the existence of other dimensions and consequently the influences they may cause, favors an expansion of the perspective, and also brings a detailing about the external factors (organization, society and culture) that influence the dual career couple. To consider that this couple, as well as having personal challenges in the relationship between work and family, is subject to the culture that regulates their roles (men and women) and that directly influences how organizations will handle that topic reveals the merit of this study. This, in turn, draws attention to the organizational sphere and shows that it cannot be detached from this reality. Considering that people management policies, that include dual career couples, are emerging.